Local scour within a gradual open channel expansion - Ng, Siang Cheng. (2012)
Few research were done on gradual channel experiment. In this experiment, the study of local scour within a gradual open channel expansion is presented to understand and investigate the geometry of scour hole formed under different flowrate due to the phenomenon of scouring. One type of laboratory experiment were run and observed.